2015
DOI: 10.1007/s10439-015-1312-9
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Brain Morphologies from Axonal Elongation

Abstract: Understanding the characteristic morphology of our brain remains a challenging, yet important task in human evolution, developmental biology, and neurosciences. Mathematical modeling shapes our understanding of cortical folding and provides functional relations between cortical wavelength, thickness, and stiffness. Yet, current mathematical models are phenomenologically isotropic and typically predict non-physiological, periodic folding patterns. Here we establish a mechanistic model for cortical folding, in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 59 publications
5
84
2
Order By: Relevance
“…With this idea in mind, the past several years have witnessed computational modeling evolving into an influential technique for validating or verifying experimental results, supporting and augmenting analytical models31. For example, finite element (FE) analysis has offered noteworthy insights into the growth, instability, morphogenesis, and functions of the brain3233. Recent 2D and 3D FE models have been designed and implemented to elucidate the role of mechanical parameters during brain development2331.…”
mentioning
confidence: 99%
“…With this idea in mind, the past several years have witnessed computational modeling evolving into an influential technique for validating or verifying experimental results, supporting and augmenting analytical models31. For example, finite element (FE) analysis has offered noteworthy insights into the growth, instability, morphogenesis, and functions of the brain3233. Recent 2D and 3D FE models have been designed and implemented to elucidate the role of mechanical parameters during brain development2331.…”
mentioning
confidence: 99%
“…With 80 elements along the circumference, this is the finest discretization that still runs on a single laptop computer, and yet captures the folding pattern with five to 15 elements per wavelength. We assume elastic parameters of µ w = 3kPa and λ w = 33kPa, an elastic stiffness ratio of E g /E w = 3 and a growth ratio of G g /G w = 1/10 [29]. Figure 3 illustrates the emerging pattern formation of a growing shell on a spheroidal substrate for varying radius-tothickness ratios R/t at fixed semi-axes R x = R y = R and R z = 1.2R.…”
Section: Continuum Model Of Growing Bi-layered Systemmentioning
confidence: 97%
“…3) [Marieb and Hoehn, 2012]. This peculiar shape is the result of tangential expansion of the cortical layer relative to the sublayers that generates compressive stress, leading to the mechanical folding of the cortex, which is submersed in liquid which in turn provides external pressure [Richman et al, 1975;Toro and Burnod, 2005;Nie et al, 2010;Xu et al, 2010;Bayly et al, 2013Bayly et al, , 2014Budday et al, 2014;Ronan et al, 2014;Tallinen et al, 2014;Holland et al, 2015;Striedter et al, 2015]. Modeling brain convolution development by physical experiments and mathematical simulations [Tal- , 2016] has shown that the human brain is likely to have small interindividual variations in shape, tissue properties and growth rates, and the sensitivity of mechanical folding to such variations could explain the variability of gyrification patterns, although primary convolutions are consistently reproducible in their location and timing.…”
Section: Convolutions In the Brainmentioning
confidence: 99%